An Update on Antitumor Efficacy of Catechins: From Molecular Mechanisms to Clinical Applications - Fokou, Patrick Valere Tsouh; Pone, Boniface Kamdem; Appiah-Oppong, Regina; Ngouana, Vincent; Bakarnga-Via, Issakou; Woutouoba, David Ntieche; Calina, Daniela (Wiley, 2025)
Carcinogenesis is the process by which substances that cause cancer (carcinogens) produce cancer. Extensive research conducted in recent years shows that the risk of developing certain cancers can be reduced by eating a variety of fruits and vegetables regularly. Catechins, which are more prevalent in foods and beverages made from plants, are known to have anti-cancer effects. Detailed mechanistic studies are helpful in understanding the inhibitory effects of catechins on carcinogenesis and providing background information for evaluating the effects of catechins on human carcinogenesis. This article provides an overview of catechins and their potential roles in cancer prevention and treatment, focusing on how they alter signaling pathways, slow cell proliferation, and trigger apoptosis. Also, this article discusses molecular modifications of epigallocatechin gallate and catechins as well as delivery methods based on nanostructures.
Keywords: catechins; chemoprevention; molecular mechanisms; oncology; pharmacodynamics; polyphenols; therapeutics